2022
DOI: 10.1159/000524671
|View full text |Cite
|
Sign up to set email alerts
|

Does the Addition of Radial Endobronchial Ultrasound Improve the Diagnostic Yield of Electromagnetic Navigation Bronchoscopy? A Systematic Review

Abstract: <b><i>Background:</i></b> Lung cancer is the leading cause of cancer-related death worldwide. Early diagnosis is crucial to increased survival rates. Radial endobronchial ultrasound (rEBUS) and electromagnetic navigation bronchoscopy (ENB) have been developed for the diagnosis of small lung lesions. The aim of this systematic review was to evaluate whether the combination of rEBUS and ENB is superior to ENB alone. <b><i>Method:</i></b> A systematic search was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Moreover, the observation of smaller nodule sizes in the combination group suggests a possible inclination toward using the combination in challenging cases. Given that most of the previous literature has already shown that combining the two methods leads to better results but also increases costs and complication rates, we hypothesized that the combination may be unnecessary for simple cases 13–16 . Hence, it was identified that the characteristics correlated with a reduced diagnostic yield, and an additional subgroup analysis was conducted by specifically selecting nodules based on the outcomes of the multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the observation of smaller nodule sizes in the combination group suggests a possible inclination toward using the combination in challenging cases. Given that most of the previous literature has already shown that combining the two methods leads to better results but also increases costs and complication rates, we hypothesized that the combination may be unnecessary for simple cases 13–16 . Hence, it was identified that the characteristics correlated with a reduced diagnostic yield, and an additional subgroup analysis was conducted by specifically selecting nodules based on the outcomes of the multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This allows an operator to confirm whether the target has been reached by providing ultrasound images 12 . Combining ENB and RP‐EBUS seems beneficial because it enables the performer to determine the correct bronchus, approach the lesion using ENB, and then confirm the lesion using RP‐EBUS 13 . Most previous studies have shown consistent results, suggesting that combining the two methods would be advantageous 14–16 .…”
Section: Introductionmentioning
confidence: 93%
“…Another meta-analysis examined the additional advantage of R-EBUS (1.4 mm, 20 MHz, UM S20-17S; Olympus) in combination with ENB (SuperDimension). However, the results were not suitable for metaanalysis because of study heterogeneity and small sample sizes [15]. SuperDimension and Bronchus software were used to navigate to the target nodule, and an extended working channel (EWC) was lodged into the target lesion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that factors such as lesion size, radial endobronchial-ultrasound (rEBUS) and proximity to the hilum, as well as computed tomography (CT) bronchus sign (air-filled bronchus near the lesion as seen on CT), increase diagnostic yield in conventional bronchoscopy [ 3 , 4 , 5 , 6 ]. Although some studies have suggested that this is also the case in ENB [ 7 , 8 ] the conclusions have been based on data from operators with substantial prior experience in ENB.…”
Section: Introductionmentioning
confidence: 99%